# How do you solve #-6n-2n=16#?

Combine like terms

Simplify

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation -6n - 2n = 16, you first combine like terms to simplify the left side: -6n - 2n = -8n. Then, isolate the variable by adding 8n to both sides of the equation: -8n + 8n = 16 + 8n. Simplify further: 0 = 16 + 8n. Subtract 16 from both sides: 0 - 16 = 16 + 8n - 16. Simplify: -16 = 8n. Finally, divide both sides by 8 to solve for n: -16/8 = 8n/8. Simplify: -2 = n. Therefore, the solution to the equation is n = -2.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7